Association of TNF-α and IL-6 Concentrations with Depression in Patients with Rheumatoid Arthritis - Jelena Mrđa; Ljiljana Tadić-Latinović; Ljubinka Božić Majstorović; Vladimir Mrđa; Bosa Mirjanić-Azarić; Irma Ovčina; Semir Vranić; Snježana Popović-Pejičić (Current Issues in Molecular Biology)
Background/Aim: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease, characterized by the production of numerous pro-inflammatory cytokines, such as tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β), which lead to pathophysiological changes in innate and acquired immunity. The existing evidence shows that pro-inflammatory cytokines in rheumatoid arthritis impact monoaminergic neurotransmission, neurotropic factors, and synaptic activity, which may lead to the development of depression. Materials and Methods: In our study, we explored the association between TNF-α and IL-6, disease activity, and the degree of depression in patients with RA. The association between TNF-α and IL-6 and the Beck and Hamilton depression scales was analyzed in a group of 116 RA patients with depression. We investigated the same correlation in 45 patients with primary depression who represented the control group. Results: A Spearman test showed that IL-6 levels had a positive association with the Beck and Hamilton scales (p < 0.05) and that TNF-α had a positive association with the Hamilton scale (p < 0.05). Also, the Hamilton depression scale was the more sensitive scale in the detection of depressive symptoms. Conclusions: Our study indicates that elevated values of pro-inflammatory cytokines are associated with the degree of depression in patients with RA. Future preclinical and clinical studies will contribute to a better understanding of the pathophysiological mechanism of depression in patients with RA and may serve as the basis for new treatment modalities. By detecting depression promptly, with the help of the HAM-D as the more sensitive scale, we could influence the future modality of treatment, and with a multidisciplinary approach, we could ensure an improvement in the quality of life of patients with RA.